2020
DOI: 10.1038/s41598-020-72070-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil erodibility indices under different land uses in Ri-Bhoi district of Meghalaya (India)

Abstract: In absence of soil erosion plots for determination of erodibility index (K) for erosion models like Universal Soil Loss Equation (USLE) or Revised Universal Soil Loss Equation (RUSLE) to estimate soil erosion, empirical relations are used. In the present study, soil erodibility index was determined for entire Ri-bhoi district of Meghalaya based on soil physical and chemical properties through empirical relationship and presented in a map form. Dominant land uses of the district were identified through geo-spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 26 publications
(35 reference statements)
0
22
0
2
Order By: Relevance
“…Factors that influence aggregate stability are important in evaluating the ease with which soils erode by water and/or wind, the potential of soils to crust and/or seal, soil permeability, quasi-steady state infiltration rates and seedling emergence and in predicting the capacity of soils to sustain long-term crop production [4]. Apart from quantitative indices for soil erodibility to estimate soil erosion some other indices are also used by researchers to understand the proneness of soil to erosion [29]. The soil aggregate stability index (ISS) developed by [30] have been widely used to assess soil structural degradation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that influence aggregate stability are important in evaluating the ease with which soils erode by water and/or wind, the potential of soils to crust and/or seal, soil permeability, quasi-steady state infiltration rates and seedling emergence and in predicting the capacity of soils to sustain long-term crop production [4]. Apart from quantitative indices for soil erodibility to estimate soil erosion some other indices are also used by researchers to understand the proneness of soil to erosion [29]. The soil aggregate stability index (ISS) developed by [30] have been widely used to assess soil structural degradation.…”
Section: Methodsmentioning
confidence: 99%
“…Critical level of organic matter (CLOM) is also an indicator of erosion susceptibility [29]. Its estimation is If the value of CLOM is less than 5%, it is indicated that soil loses its structure and becomes highly susceptible to erosion.…”
Section: Methodsmentioning
confidence: 99%
“…The clay ratio of soil, calculated as the percentage of sand and silt fractions over the percentage of clay, is used as an index of soil erodibility [70], with low clay-ratio soils considered to have a low erodibility and higher-ratio soils to be more erodible [70]. Except in the Sile, where the clay ratio is increasing as the GLDs decrease, no clear relation between clay ratio and density was observed in the other three catchments (Appendix A Figure A3).…”
Section: Lithologic and Soil Controlsmentioning
confidence: 99%
“…e dried-up part of the reservoir was designated as the study area, where sediment samples were picked from ten different locations (Figure 2). e sampling points were selected randomly and geo-referenced using a hand-held Garmin GPSMAP 65s global positioning system (GPS) gadget [34]. Undisturbed soil samples were collected using core rings, whereas about two kilograms of disturbed soil was collected in appropriate bags.…”
Section: Sediment Sample Collectionmentioning
confidence: 99%